1999
DOI: 10.1292/jvms.61.183
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Hyaluronidase, Acrosin, and N-Acetylhexosaminidase Activities of Dog Sperm after Incubation.

Abstract: ABSTRACT. Hyaluronidase, acrosin and N-acetylhexosaminidase activities were examined in sperm collected from 12 beagle dogs and in culture medium after 0.5 hr and 7 hr of sperm incubation. The activities of the three enzymes were significantly higher at 7 hr than at 0.5 hr (P<0.05, 0.01), and the increases were associated with sperm capacitation. It was considered that the three enzymes in the dog sperm are related to fertilization by reason of the findings of the release of these enzymes from the sperm into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…However, fresh spermatozoa retained their acrosin activity over time, since the presence and the sizes of gelatin halos increased throughout incubation periods. This increasing gelatin digestion observed in fresh samples agrees well with the results of Kawakami et al, (1999), who concluded that acrosin activity in fresh dog sperm, measured with light spectrophotometry, increased in association with sperm capacitation.…”
Section: Discussionsupporting
confidence: 91%
“…However, fresh spermatozoa retained their acrosin activity over time, since the presence and the sizes of gelatin halos increased throughout incubation periods. This increasing gelatin digestion observed in fresh samples agrees well with the results of Kawakami et al, (1999), who concluded that acrosin activity in fresh dog sperm, measured with light spectrophotometry, increased in association with sperm capacitation.…”
Section: Discussionsupporting
confidence: 91%
“…Since almost all canine sperm that penetrate cumuli have an acrosome cap, acrosome-intact dog sperm, but not acrosome-reacted sperm, may be able to penetrate the cumuli as in hamster sperm [37] and pig sperm [22]. The authors have reported that canine sperm release hyaluronidase, an enzyme that hydrolyzes the hyaluronic acid component of the cumulus intercellular matrix [18], and the acrosome reaction of canine sperm is induced by homologous ZP [20], the same as in mouse [12], hamster [27], pig [4] and bull [23]. In the present study, it was shown that hyperactivated movement of canine sperm is induced by homogenated cumuli, as in hamster sperm [13].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that canine hyperactivated sperm with intact acrosome can penetrate homologous cumuli and that the sperm are able to pass through the cumulus because the hyperactivated movement is maintained by hyaluronic acid secreted by the cumulus cells. Therefore, the hyperactivated movement of sperm that have penetrated a cumulus may be maintained by hyaluronic acid, which is also the main component of the cumulus intercellular matrix in many species [1,10,25,28].Sperm penetration into cumuli in many species [24] is made possible by the release of hyaluronidase, an enzyme that hydrolyzes hyaluronic acid, from the sperm head, and the authors have reported that canine sperm also release hyaluronidase [18]. It has been discovered that hamster acrosome-reacted sperm can not penetrate cumuli [5,7] and that the acrosome reaction is induced by homologous zona pellucida (ZP) [27], but there have been no reports on detailed investigation of the relationship between canine sperm and homologous cumuli during fertilization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors had previously found that hyaluronidase and Nacetylhexosaminidase, the enzymes which hydrolyze GAGs, are present in dog sperm and that they are released during capacitation [14]. Thus, the GAGs in the fluid secreted by the genital organs of bitches may serve to accelerate the capacitation of dog sperm.…”
Section: Discussionmentioning
confidence: 99%